Have a Nice day A Case for Sunbathing - Bragado, Igor; Gertler, Miles (Re-visiones, 2025)
This graphic essay reflects on the concepts developed for Common Accounts’ installation Have a Nice Day, a solar canopy and artificial sun presented at MUDAC’s Solar Biennale in 2025. The essay intersperses images of the installation with transcripts of narration sourced from influencer testimonials and Georges Bataille’s “The Accursed Share,” staging a critical encounter between contemporary domestic therapeutic devices and Bataille’s theory of excess solar energy. Through this juxtaposition, “A Case for Sunbathing” examines how artificial sunlight has been theorized in popular consumer advertising and wellness-oriented social media for applications as diverse as cellular rehabilitation, anti-aging, and enhanced fertility. Taking Have a Nice Day as a conceptual scaffold, the paper follows how the installation troubles psycho-social associations with the sun in an age of climate anxiety, channeling them into sensible, energetic encounters in the gallery and tracing their entanglement with optimization, self-design, planetarity, technology,and daily life.